2012
DOI: 10.1536/ihj.53.391
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Hyponatremia by Tolvaptan Before Left Ventricular Assist Device Implantation

Abstract: SummaryHypervolemic hyponatremia is often complicated with advanced heart failure together with increased excretion of sodium by diuretics. Tolvaptan, an oral vasopressin-2-receptor antagonist, has been previously reported to improve congestion and correct hyponatremia through increased excretion of free water. However, there is little evidence concerning the administration of tolvaptan in patients with stage D heart failure. We experienced 2 patients with stage D heart failure who received 3.75 mg/day of tolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] In contrast, we sometimes experience TLV-non-responders in our daily clinical practice. 11) We previously proposed a novel predictor of responsiveness to TLV, ie, the baseline urine aquaporin-2 (U-AQP2) level relative to the plasma AVP (P-AVP) level, which may indicate a preserved vasopressin type 2 receptor (V2R)-related signaling pathway in the principal cells of the renal collecting duct.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] In contrast, we sometimes experience TLV-non-responders in our daily clinical practice. 11) We previously proposed a novel predictor of responsiveness to TLV, ie, the baseline urine aquaporin-2 (U-AQP2) level relative to the plasma AVP (P-AVP) level, which may indicate a preserved vasopressin type 2 receptor (V2R)-related signaling pathway in the principal cells of the renal collecting duct.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] We also reported the effi cacy and safety of TLV in (1) amelioration of congestion even in stage D HF patients and (2) improvement of renal function by converting ongoing diuretics to TLV. 8,9) With respect to serum sodium concentration (S-Na), various studies in Europe and the United States have demonstrated the effi cacy of TLV to improve hyponatremia with little chance of hypernatremia, ie, S-Na > 145 mEq/L (eg, 1.7% of hypernatremia in the EVEREST study and 0% in the QUEST study). 2,6,[10][11][12] In Japan, we can administer TLV to HF patients to treat their congestion regardless of baseline S-Na as long as hypernatremia or rapid increases in S-Na do not develop.…”
mentioning
confidence: 99%
“…Recently, TLV has been demonstrated to be advantageous in the correction of hyponatremia, 11,12) stabilization of hemodynamic state, 13) and amelioration of congestion without a worsening of renal function. 14) Administration of TLV along with discontinuation of trichlormethiazide successfully reversed his hyponatremia and renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%